Reconceptualizing Academic Supervision and Teacher Performance: An Empirical Study in Public Secondary School Management - Ananda Sabilla Nurfariza; Kunalan Kuriaya (International Journal of Advanced Studies in Educational Management (IJASEM), 2026)
Improving teacher performance remains a central issue in educational quality, particularly in developing countries where instructional effectiveness is closely linked to school leadership practices. Academic supervision conducted by school principals is considered a strategic mechanism for fostering teacher professionalism and improving classroom practices. This study aims to examine the effect of principals’ academic supervision on teacher performance at a public senior high school in Indonesia. A quantitative explanatory design with a survey approach was employed. The population consisted of all 48 teachers, who were selected using a saturated sampling technique. Data were collected through validated Likert-scale questionnaires and analyzed using descriptive statistics and simple linear regression. The results reveal that academic supervision has a positive and significant effect on teacher performance (R² = 0.425; p < 0.05), indicating that effective supervision contributes to improvements in lesson planning, instructional implementation, assessment, and follow-up activities. These findings highlight the role of structured and continuous supervision as a professional development tool rather than merely an administrative function. This study contributes to the growing body of research on instructional leadership by providing empirical evidence on how academic supervision strengthens school quality culture and teacher performance, and offers practical implications for optimizing supervisory programs to enhance learning quality.